Dispute resolution in sport athletes, law, and arbitration - McArdle, David (Ethics and sport)
This book explores the development of alternative dispute resolutions in sports by examining the legal frameworks within which sports arbitration systems operate, considering their similarities with other arbitral bodies and the extent to which ADR in sport can be seen as a consequence of, and perhaps a solution to, the 'juridification' of sports.